2014
DOI: 10.1007/s10404-014-1493-9
|View full text |Cite
|
Sign up to set email alerts
|

Free-molecular gas flow through the oscillating membrane

Abstract: the main distinguishing features of the track membranessmall thickness and high uniformity of the pore size.In this paper, the possibility of using a high-frequency oscillating track membranes as diffusion membranes for gas separation was studied. High-frequency forced oscillation of the membrane was considered because of assumption that the membrane conductivity for a given gas can be controlled by varying the frequency and amplitude of oscillation. The problem about free-molecular gas flow through a oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…For detailed description, refer to [4]. Assumption that all membrane channels are equal and membrane moves as absolutely rigid body implies that flow can be studied only in one channel.…”
Section: Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For detailed description, refer to [4]. Assumption that all membrane channels are equal and membrane moves as absolutely rigid body implies that flow can be studied only in one channel.…”
Section: Computationsmentioning
confidence: 99%
“…Other important application is the construction of novel separation devices working in microgravity [3]. In authors' previous papers [4,5] a novel effect of gas separation using track membranes oscillating with high frequency was discovered; it was shown that varying the amplitude and frequency of oscillations one can control the conductivity of the membrane for the given gas, and as a result, achieve the effect of gas separation. The purpose of the present work is to determine optimal values of membrane oscillation parameters for the most efficient gas separation.…”
Section: Introductionmentioning
confidence: 99%
“…For detailed description, please refer to [7]. Assumption that all membrane channels are equal and membrane moves as absolutely rigid body implies that flow can be studied only in one channel.…”
Section: Computationsmentioning
confidence: 99%
“…The computation was as follows. The same way as in [7], coordinate and velocity of a new gas molecule at the inlet section of the channel were calculated according to given distributions. Then, the point of collision between gas molecule and channel wall was calculated.…”
Section: Computationsmentioning
confidence: 99%
See 1 more Smart Citation